Pengaruh Brand Image terhadap Keputusan Pembelian Sepeda Motor Honda Spacy pada PT. Patria Anugrah Sentosa Beringin Jambi - Muhammad Agung Prabowo (Science of Management and Students Research Journal (SMS), 2020)
This Study was intended to know the effect of brand image on the purchasing decision of Honda spacy motorcyleat PT patria anugrah sentosa beringin jambi. Based on the data obtained from this study, the sale of honda spacy motorcyleat PT Patria Anugrah Sentosa Beringin Jambi has fluctuated during the period 2014 to 2018. Data retrieval method by random sampling, data collection is done by questionnaires and interviews, the analysis use dissimple linear regression analysis, correlation coefficient, coefficient of determination and statisticalt est t.  PT Patria Anugrah Sentosa Beringin Jambi islimitedliability company engaged in large tradesuch as automotive motorbikes, partsand accessoris. PT.Patria Anugrah Sentosa Beringin Jambi commenced operations in 2012 located in Jl. H.Adam, the area of operation located in Jambi City. Brand image have a positive and significant effect on puchasing decisions with a regression coefficient of 0,670. This is evidenced by the results of the t-test analysis which shows the value of tcount7,479 > ttablevalue 2,00172 and the significance level of 0.000<0.005 significance probability α = 0,5. Consumers agree with brand image Honda Spacy motorcycle productsproducedbayPT.Ptria Anugrah Sentosa Beringin Jambi. The consumer agress with the purchase decision on the purchase of Spacy Honda productions produced PT.Patria Anugrah Sentosa Beringi Jambi.